Teknik Casting Pada Perhiasan Guna Menunjang Daya Beli - Pandansari Kusumo (Institut Seni Indonesia Yogyakarta, 2015)
Along with the development of jewelry in Indonesia, several techniques of making are used. in the design of industrial products, jewelry by casting tehcniques is one of the techniques of making jewelry of bulk; using several models of jewelry will obtain many products of casting at the same time. This casting technique is very supportive in the process of production, working efficiently and also cost efficient. But when the jewelry products are made manually, it will not achieve high productivity results as expected.Keyword: casting technique, efficently, high productivity